Chapter 25 What Difference Does a Railroad Make? Transportation and Settlement in the BAM Region in Historical Perspective - Povoroznyuk, Olga (Taylor & Francis, 2023)
In pre-Soviet and early Soviet times, the northern areas of East Siberia and the Russian Far East that today are crossed by the Baikal-Amur Mainline were more or less exclusively the domain of semi-nomadic Evenki reindeer herders and rarely traversed by Russian or other European travelers. The decision to build a railroad line through this region during the 1970s and 1980s could not but have tremendous social, demographic, and ecological impacts. The specific impacts of the BAM cannot be understood, however, without considering the political and economic environments in which construction took place. This chapter is based on archival materials and interviews collected during multiple fieldwork visits during the 2010s, with a focus on the city of Tynda, the "capital" of the BAM, as well as the city Severobaikal'sk and the town of Novaia Chara along the railroad, and the Indigenous villages of Pervomaiskoe and Chapo-Ologo located not far from the BAM. The chapter's aim is to provide tentative answers to the title question and to explore the opportunities and constraints, or "affordances," of infrastructure as an agent of change.